2010
DOI: 10.1177/0020764010382369
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variations in pathways to acute care and compulsory detention for women experiencing a mental health crisis

Abstract: Background: Much recent debate on excess rates of compulsory detention and coercive routes to care has focused on young black men; evidence is less clear regarding ethnic variations among women and factors that may mediate these.Aim: To explore ethnic variations in compulsory detentions of women, and to explore the potential role of immediate pathways to admission and clinician-rated reasons for admission as mediators of these differences.Method: All women admitted to an acute psychiatric inpatient ward or a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…As in other studies, we confirm that immigrants have a high rate of compulsory presentation to mental health emergency departments [17,26,27]. In psychiatry, the main clinical examination tool is language, a fact that sometimes raises barriers in care provision.…”
Section: Discussionsupporting
confidence: 88%
“…As in other studies, we confirm that immigrants have a high rate of compulsory presentation to mental health emergency departments [17,26,27]. In psychiatry, the main clinical examination tool is language, a fact that sometimes raises barriers in care provision.…”
Section: Discussionsupporting
confidence: 88%
“…One UK study [25] showed higher rates of detention in this group (non-FEP women). The group in this study is very heterogeneous, including Turkish, Polish and Irish patients.…”
Section: Discussionmentioning
confidence: 98%
“…These factors have been demonstrated as potentially accounting for some of the variation between ethnic groups in rates of being detained in previous studies [3,25,26]. Logistic regression analysis was conducted on the subgroup to explore if ethnic differences in rates persisted when adjustments were made for pathway to care and help-seeking behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have, however, found that the higher risk of detention amongst minority patients is considerably reduced or even eliminated if sociodemographic, clinical and care pathway differences are taken into account (Bebbington et al 1994;Cole et al 1995;Lawlor et al 2012).…”
Section: Introductionmentioning
confidence: 99%